2000
DOI: 10.1001/archpsyc.57.11.1039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Interpersonal Psychotherapy for Postpartum Depression

Abstract: These findings suggest that IPT is an efficacious treatment for postpartum depression. Interpersonal psychotherapy reduced depressive symptoms and improved social adjustment, and represents an alternative to pharmacotherapy, particularly for women who are breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
282
1
13

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(309 citation statements)
references
References 36 publications
13
282
1
13
Order By: Relevance
“…The group effect may particularly facilitate the reporting of symptoms and gathering support from the partner/family and decreasing social isolation. Our results were consistent with findings from a study on interpersonal therapy [31] that identified skills to resolve marital disputes and major role transitions as important elements in treatment and with findings from epidemiological studies looking into predictors of PPD [32,33,34,35]. Companionship and belonging to a group of similar people may have a protective effect.…”
Section: Discussionsupporting
confidence: 91%
“…The group effect may particularly facilitate the reporting of symptoms and gathering support from the partner/family and decreasing social isolation. Our results were consistent with findings from a study on interpersonal therapy [31] that identified skills to resolve marital disputes and major role transitions as important elements in treatment and with findings from epidemiological studies looking into predictors of PPD [32,33,34,35]. Companionship and belonging to a group of similar people may have a protective effect.…”
Section: Discussionsupporting
confidence: 91%
“…Interpersonal Psychotherapy (IPT; 16 sessions) has demonstrated efficacy in treating acute depression, 56,57,58 preventing depressive relapse through maintenance, 59,60 treating antenatal and postpartum depression, 38,45,61 and treating depression in primary care. 62 A brief version of IPT has been developed 63 and has received empirical support in a number of studies of pregnant and parenting women with depression.…”
Section: Methodsmentioning
confidence: 99%
“…It has proven effective for PND in controlled trials with large sample sizes, different comparison groups, and individual and group settings (Grote et al, 2009;O'Hara, et al, 2000;Miniati et al, 2014;Spinelli, & Endicott, 2003). IPT is therefore a PND treatment which has the potential to directly address maternal sensitivity in a similar manner to the attachment-based therapies.…”
Section: Interpersonal Therapy Is a Relationship-focussed Pnd Treatmentmentioning
confidence: 99%